Hubungan Adversity Quotient dengan Work Readiness pada Mahasiswa Tingkat Akhir Fakultas Psikologi Universitas Negeri Padang - Jeni Fadhila; Zulian Fikry (Pusat riset dan Inovasi Nasional, 2025)
Competition in the job market has been increasing every year, demanding high-quality human resources who are capable of adapting to rapid changes in the era of Industry 5.0. However, recent findings indicate that many graduates, particularly those from the class of 2024, still lack sufficient work readiness, contributing to a relatively low work readiness rate in Indonesia. Work readiness is a crucial attribute that determines the extent to which graduates can transition smoothly from academic settings into professional environments. One of the psychological constructs believed to influence this readiness is the Adversity Quotient (AQ), which reflects an individual’s ability to withstand, adapt, and grow in the face of challenges and difficulties. The purpose of this research is to analyze the relationship between adversity quotient and work readiness among 174 final-year students of the Psychology Faculty at Universitas Negeri Padang. This study employed a quantitative research design with a purposive sampling technique. The Work Readiness variable was measured using a scale developed by the researcher based on Caballero et al. (2011), while the Adversity Quotient was measured using the adapted Adversity Response Profile scale from Stoltz (2000). Based on the results of product moment correlation analysis, findings show that the adversity quotient has a strong and positive correlation (r = 0.691) with work readiness. These results highlight the importance of strengthening resilience and adversity management skills to ensure that students are better prepared to enter the workforce with confidence and competence.